(3GdHSGWs - (3GdMSf Hf Ydj Hf GdMSf Hf Ydj Hf YeQ GdCTQa Hf Ydj Hf Rjf GdYGHOjf GdSHW GdYdhj, GdfGUQ GdCWQhT,J (B330 (3g` s
(3ChdgG (B:s
(3hLYdg HSGWkG hOdjdkG ddeJYdejf ai Gdbhd HGdJhMjO ddg hddYOd efg Ydi YHGOI ai eG GMceI haQVI ef GdOjf s
(3BNQgG (B:s
(3cGdfajS GdPi VjYI ef GdGNQg HCOi Je cJGH GdHSGW s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJhcdjI GdjefjI HGdLGeY GdcHjQ UfYGA (B((3Yde cdGe (B96) s
Keywords: (3eJaQbGJs